2018
DOI: 10.1038/s41388-018-0457-z
|View full text |Cite
|
Sign up to set email alerts
|

TIP60-dependent acetylation of the SPZ1-TWIST complex promotes epithelial–mesenchymal transition and metastasis in liver cancer

Abstract: Metastasis is the main cause of cancer mortality. However, the triggering mechanisms and regulation of epithelial-mesenchymal transition (EMT) factors in the commitment of metastasis have not been well characterized. Spermatogenic Zip 1 (SPZ1) acts as a proto-oncogene and an upstream regulator of EMT during tumorigenesis. Here we report that the HIV-1 Tat-interacting protein 60 kDa (Tip60) acetyltransferase mediates acetylation at lysine residues of SPZ1 at positions 369 and 374, and of TWIST1 at positions 73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…25) EMT promotes migration by downregulating E-cadherin and up-regulating transcription factors such as TWIST, Snail and Integrin. [26][27][28] Liu et al found that the Chinese medicinal herbal preparation Jianpijiedu (JPJD) inhibits TGF-β/Smad activity, stabilizes Snail, and up-regulates E-cadherin, thereby inhibiting EMT, tumor invasion, and metastasis. 29) Curcumin, which is derived from the rhizome of turmeric (Curcuma longa), prevents EMT progression in intestinal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…25) EMT promotes migration by downregulating E-cadherin and up-regulating transcription factors such as TWIST, Snail and Integrin. [26][27][28] Liu et al found that the Chinese medicinal herbal preparation Jianpijiedu (JPJD) inhibits TGF-β/Smad activity, stabilizes Snail, and up-regulates E-cadherin, thereby inhibiting EMT, tumor invasion, and metastasis. 29) Curcumin, which is derived from the rhizome of turmeric (Curcuma longa), prevents EMT progression in intestinal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we demonstrated that BRD4 is not only required for gastric cancer cell proliferation, but also essential for invasion and metastasis in vitro and in vivo. A role of BRD4 in cancer metastasis was recently implicated in the zinc finger MYND-type containing 8 (ZMYND8)-mediated control of HIF transcriptional activity (28) and Spermatogenic Zip 1 (SPZ1)-Twist1 complex-mediated cancer cell metastasis (29). BRD4 is a promising anticancer target as revealed by several loss-of-function genetic screens, and there are significant interests in development BET inhibitors for cancer therapy (30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has shown that ROS induce EMT by activating Snail expression, which then represses the expression of E-cadherin, a classical marker of the epithelial phenotype [100]. Several independent studies demonstrated that EMT can be induced by direct contact of epithelial cells with HIV proteins [24, 86, 101, 102]. To see if this is the case for 4T1luc2 cells expressing RT, we monitored them for the expression of E-cadherin , mesenchymal cell phenotype markers N-cadherin and Vimentin , and of two transcription factors, heavily involved in EMT, Twist and Snail [71, 98].…”
Section: Discussionmentioning
confidence: 99%